Comparison of Definitions of Tantrayukti Mentioned by Neelamegha Bhishak and Arunadatta - Jiji N G; Sunitha G.R (International Journal of Ayurveda and Pharma Research, 2021)
Tantrayukti is one among the techniques used by Acharyas for understanding and interpreting scientific literature of Ayurveda. Tantrayukti is defined as a methodology that helps us to interpret scientific treatise correctly and intelligently and it enables us to set optimum standardization in the interpretation of scientific material and to minimize subjective variation in understanding the treatise. There are some controversies existing regarding the enumeration and definitions of Tantrayukti. Even though names of 36 Tantrayukti mentioned by Neelamegha Bhishak, the author of Tantrayuktivichara and Arunadatta, the commentator of Ashtanga Hridaya are almost similar, there is dissimilarity existing regarding the definitions of Tantrayukti. This study is intended to make an attempt to compare definition of Tantrayukti of Neelamegha Bhishak and Arunadatta.